Value co-creation and data-driven orientation: reflections on restaurant management practices during COVID-19 in Italy. Issue 2 (29th March 2022) - Polese, Francesco; Botti, Antonio; Monda, Antonella
Abstract : Purpose: Covid-19 pandemic impacted the tourism industry worldwide. Especially in catering, where restaurateurs have had to reinvent their business models, information and communication technologies (ICTs) play a fundamental role in supporting these changes, transforming barriers into opportunities. The purpose of this study is to investigate how restaurateurs' perception of ICTs has changed before and during Covid-19 and to detect whether ICTs can be considered a tool to foster antifragility, resilience and value co-creation as ideal outcomes. Design/methodology/approach: This study presents a longitudinal study on the use of ICT platforms by Italian restaurant managers. The case study analyzed is TheFork. Data collection took place in two different rounds: before Covid-19 (year 2017) and during Covid-19 (year 2020). Findings: The findings of this study reveal how new rules imposed by the Government changed restaurant managers' attitudes towards technology. In 2017, restaurateurs showed reticence towards technology, not used in a strategic way; today, everyone uses ICT to improve business. Originality/value: The study shows that ICT platforms enable antifragility, resilience and value co-creation, creating a service ecosystem supporting restaurant management.